Carrier Accumulation in Graphene with Electron Donor/Acceptor Molecules. (15th May 2015) - Akiyoshi, Hidehiko; Goto, Hidenori; Uesugi, Eri; Eguchi, Ritsuko; Yoshida, Yukihiro; Saito, Gunzi; Kubozono, Yoshihiro
<x xml:space="preserve">Abstract</x> Electron transfer between graphene and an adsorbed molecule is systematically studied using a variety of electron acceptor/donor molecules. Doping efficiency is determined by the difference between the Fermi energy of graphene and the lowest unoccupied molecular orbital or highest unoccupied molecular orbital level of the molecule. The maximum carrier density accumulated by molecular adsorption is limited by the small density of states in graphene.